2012
DOI: 10.5897/ajb11.2287
|View full text |Cite
|
Sign up to set email alerts
|

Improving salinity tolerance of Acacia saligna (Labill.) plant by arbuscular mycorrhizal fungi and Rhizobium inoculation

Abstract: This study was carried out to investigate the alleviation of salt stress (0, 6.25, 12.50 and 25 dS/m) on growth and development of Acacia saligna, grown in sandy loam sterile soil by using arbuscular mycorrhizal fungi (AMF) and Sinorhizobium terangae (R), individually or in combination (AMF+R). Growth and nodulation parameters, leaf osmotic adjustment and chemical analysis were used as parameters. Salt stress increases the percentage of sodium (Na) and calcium (Ca) contents as well as proline; meanwhile, it re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Similar results were recently proved in mixed-species plantations of Eucalyptus and Acacia (Tchichelle et al, 2017). Moreover, A. cyanophylla was previously reported to exhibit a large number of nodules on the root system and to form symbioses with a higher number of Rhizobia strains (Amira et al, 2012;Bouazza et al, 2015;Birnbaum et al, 2017). The exotic shrub A. cyanophylla has shown its primordial role in maintaining and improving the chemical and biological fertility of the soil in the sand dunes ecosystem of Essaouira (Kavroulakis et al, 2020;Lozano et al, FIGURE 3 | Relative abundance of each AMF morphotype in rhizospheric soils of Acacia cyanophylla and in the control (bare soil) in the sand dune of Essaouira.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar results were recently proved in mixed-species plantations of Eucalyptus and Acacia (Tchichelle et al, 2017). Moreover, A. cyanophylla was previously reported to exhibit a large number of nodules on the root system and to form symbioses with a higher number of Rhizobia strains (Amira et al, 2012;Bouazza et al, 2015;Birnbaum et al, 2017). The exotic shrub A. cyanophylla has shown its primordial role in maintaining and improving the chemical and biological fertility of the soil in the sand dunes ecosystem of Essaouira (Kavroulakis et al, 2020;Lozano et al, FIGURE 3 | Relative abundance of each AMF morphotype in rhizospheric soils of Acacia cyanophylla and in the control (bare soil) in the sand dune of Essaouira.…”
Section: Discussionsupporting
confidence: 85%
“…These two types of symbiosis are traditionally known for their undeniable respective roles in phosphate and nitrogen nutrition. The levels of available phosphorus and total nitrogen in rhizospheric soils bear witness to these effects (Amira et al, 2012;Yusoff et al, 2019). In the current work, the phosphorus contents are twice as high and the total nitrogen contents are four times higher compared to a non-rhizosphere soil without the influence of the roots of A. cyanophylla.…”
Section: Discussionmentioning
confidence: 46%
“…This is mainly related to greater nutrient acquisition, total chlorophylls, carbohydrates, and proline contents elevated K/Na ratios in root and shoot tissues, and changes in root morphology [109,124] in mycorrhizal plants as compared nonmycorrhizal plants. These results were more significant when salt-stressed plants were co-inoculated with selected rhizobium strains, ectomycorrhizal fungi and/or endophytic bacteria, in addition to AMF [86,123,125]. Nevertheless, it should be mentioned that in studies where different strains were tested, the extent of AMF response on plant growth as well as root colonization varied with fungal species, and with the level of salinity [126].…”
Section: Less Oxidative Damage Promoted Plant Growth and Enhancedmentioning
confidence: 95%
“…Zea mays plants inoculated separately with three native AMF showed better biomass production and higher shoot potassium and proline contents, as compared to non-mycorrhizal plants [119]. It has also been demonstrated that AMF alleviates the deleterious effects of salt on plants growth in Acacia species [109,122,123]. This is mainly related to greater nutrient acquisition, total chlorophylls, carbohydrates, and proline contents elevated K/Na ratios in root and shoot tissues, and changes in root morphology [109,124] in mycorrhizal plants as compared nonmycorrhizal plants.…”
Section: Less Oxidative Damage Promoted Plant Growth and Enhancedmentioning
confidence: 96%
“…The increase in saline-induced leaf proline in these two acacia species may be due to improved proline biosynthesis and/or may be due to the inhibition of proline catabolism. The increase in leaf proline content in response to salt stress has been reported in many forest and fruit trees: Olive tree (Ahmed et al 2012), Date palm (Yaish 2015), Lemon tree (Balal et al 2011), Eucalyptus (Chaum et al 2013), Acacia auriculiformis (Patel et al 2010), Acacia saligna (Soliman et al 2012), Acacia arabica (Lassouane et al 2013), Acacia longifolia (Morais et al 2012) and Acacia senegal (Patel et al 2011). Proline production induced by salt stress has been demonstrated in halophyte and glycophyte species; except that halophytes accumulate more leaf proline under normal and stressed conditions (Himabindu et al 2016).…”
Section: Effect Of Salinity On Proline Soluble Proteins Total Free Amino Acids Starch and Reducing Sugars In Leavesmentioning
confidence: 87%